Tunable mirror and multi-channel filter based on one-dimensional exponentially graded photonic crystals - Singh B.K.; Pandey P.C. (My University, 2025)
A study on the tunability of photonic and Omni-directional band gaps has been demonstrated theoretically in one-dimensional (1-D) photonic crystals having one of the layers as exponential graded index materials and other layers of constant refractive index materials. Using numerical simulations, we have investigated the effect of relative parameters of exponential graded layers on the photonic and Omni-directional band gaps in 1-D graded photonic crystals (GPCs). We observe that the number of photonic band gaps increases with increase of the layer thicknesses and their bandwidths can be controlled by the contrast between initial and final refractive index of the graded layers. Moreover, we have studied the Omni-directional band gaps in quarter-wave and latent type layer stacking arrangements. Further, we obtained the range of refractive indices and thicknesses of constituted layers at which omnidirectional band gaps occurs. Accordingly, we find that the photonic as well as Omni-directional band gaps of desired bandwidths can be obtained by selecting appropriate parameters in GPCs. Our work will be useful in design of mirrors, channel filters, Optical sensors, Omni-directional reflectors etc. and provide more design freedom for alternative photonic devices.